'For Richer, For Poorer': Assortative Mating and Savings Preferences. (18th April 2016) - Arrondel, Luc; Frémeaux, Nicolas
Abstract : Do couples share the same values? The social sciences have mainly concentrated on comparing the socioeconomic characteristics of spouses, but rarely consider their attitudes to risk and time. In this paper, we use conventional measurements and an original method of scoring. We find that spouses are very similar in their savings preferences, even when we control for the individual characteristics. Our results suggest that most of this relationship comes from marital sorting. These conclusions are decisive in explaining the decision process within households and its implications for wealth inequalities between households since homogamy causes a divide in the population.